Feeding effectiveness of Megaphobema mesomelas (Araneae, Theraphosidae) on two prey types - Kosiba, Scott (2012)
Prey selection is essential for individual fitness; therefore, it would be expected that a predator would select prey of a higher rank (energy/time) when exposed to prey of differing quality. In this paper, we compare the feeding effectiveness (biomass consumed/time) of Megaphobema mesomelas (O. P.-Cambridge, 1892) in captivity, and the preference between two prey types: beetles and crickets. Spiders are more effective when feeding on crickets. The heavy exoskeleton of beetles increases prey-handling time in order to access a relatively smaller amount of edible tissue. Effectiveness also increases with spider and prey size (mass), with larger spiders feeding more effectively on larger prey. Spiders show a strong preference for feeding upon crickets over beetles when both prey types are offered at the same time.